Author Correction: Hepatic SATB1 induces paracrine activation of hepatic stellate cells and is upregulated by HBx - Jin Gong; Wei Tu; Jian Han; Jiayi He; Jingmei Liu; Ping Han; Yunwu Wang; Mengke Li; Mei Liu; Jiazhi Liao; Dean Tian (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.